2013
DOI: 10.1002/pssa.201228628
|View full text |Cite
|
Sign up to set email alerts
|

Change in crystalline structure and band alignment in atomic-layer-deposited HfO2 on InP using an annealing treatment

Abstract: Changes in structural characteristics and band alignments of atomic-layer-deposited HfO 2 films on InP (001) as a function of annealing temperature and film thickness were investigated using various analytical techniques. After an annealing at temperatures over 500 8C, the HfO 2 films were converted into a fully crystalline structure with a tetragonal phase with no detectable interfacial layer between the film and the InP substrate. In-P-O states, produced by interfacial reactions, were increased during the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The following equation is for possible thermodynamics in the formation of In 2 O 3 and AlPO 4 : Al species + O 2 (g) (at Al 2 O 3 –InP interface) → AlPO 4 + In 2 O 3 [Δ G ∼ (−59 kcal)] . In addition, the AlPO 4 [Δ G ∼ −1618.0 (kcal/mol)] state is more thermodynamically stable than In 2 O 3 [Δ G ∼ −198.6 (kcal/mol)] . As a consequence, AlPO 4 bonds can be generated at the Al 2 O 3 –InP interface and In 2 O 3 states can be decreased.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The following equation is for possible thermodynamics in the formation of In 2 O 3 and AlPO 4 : Al species + O 2 (g) (at Al 2 O 3 –InP interface) → AlPO 4 + In 2 O 3 [Δ G ∼ (−59 kcal)] . In addition, the AlPO 4 [Δ G ∼ −1618.0 (kcal/mol)] state is more thermodynamically stable than In 2 O 3 [Δ G ∼ −198.6 (kcal/mol)] . As a consequence, AlPO 4 bonds can be generated at the Al 2 O 3 –InP interface and In 2 O 3 states can be decreased.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure 2d-f depict the XRD patterns of each binary oxide lm with reference peaks for the representative crystalline phases for Al 2 O 3 ; JCPDS 88-0826 (hexagonal), 86-1410 (monoclinic); for HfO 2 , JCPDS 78 − 0050 (monoclinic), JCPDS 08-0342 (tetragonal); and for ZrO 2 , JCPDS 88-1007 (tetragonal), JCPDS 86-1451 (monoclinic) [41][42][43][44][45][46]. In contrast to AlO x , we demonstrated that both HfO x and ZrO x had polycrystalline structures owing to their low crystallization temperatures.…”
Section: Electrical and Materials Characterizations Of Binary Oxide T...mentioning
confidence: 99%
“…However, most of the investigations were carried out on Si wafers; only very few investigations were done on other substrates, e.g. Ge [12] or III-V [13][14][15][16][17], and/or nanostructures [18,19].…”
Section: Introductionmentioning
confidence: 99%